Pulong-niyogan island resort complex, Lopez Quezon - Alivio, Joilan S. (Manila : National University, 2000)
Pulong Niyogan is distined to be an island resort located in town of Lopez Quezon. Island were supposedly known as an island of coconut trees. Within this vicinity island comes in a tranquility of natural habitat. White sand and coral reefs covered with a 50 feet seascape enchanting and an eye catching in the attention of vacationers. And told for his attractive sceneries. In this location or spot, walking along in an island trails is a great touched in nature, avide from this putting and explore diving activities is capable to do.